The importance of store hygiene for reducing post-harvest losses in smallholder farmers' stores: Evidence from a maize-based farming system in Kenya. (January 2021) - Makinya, Kobia J.; Wagacha, John M.; Odhiambo, Judith A.; Likhayo, Paddy; Edoh-Ognakossan, Kukom; Tefera, Tadele; Abass, Adebayo; Mutungi, Christopher M.
Abstract: Knowledge of the role of hygiene in reducing food loss in farm stores is limited among extensionists, researchers, and farmers. Store hygiene practices during post-harvest handling and storage of maize were assessed using a cross-sectional survey of 342 farmers, with regular follow-up of 40 farmers' stores over seven months to measure losses caused by insects, and to score the hygiene levels using a standard checklist. Fractional Response Model was used to evaluate the associations between hygiene practices and the losses. Farmers stored their produce in sacks (98.2%) kept in outside granaries (60.1%), or rooms in dwelling houses (39.9%). Co-storage with other items — stover or animal feed (29%), old storage containers (41%), farm implements (30%), other crops (65%) and recycling of old storage bags (40%) were common practices. Nine out of ten farmers cleaned their stores before introducing the new harvest, but only half cleaned their stores during the course of storage. High hygiene scores correlated significantly with lower losses. Storing in the bedroom or living room correlated with lower losses by 2.8 and 4.6 percentage points, respectively, compared to storing it in granaries, while storage in the kitchen correlated with higher losses by 19 percentage points margin. Co-storage was associated with higher losses by 2.8 percentage points. Repairing or disinfesting the store before introducing a new harvest did not significantly reduce losses. Training in grain storage did not have a significant effect either, while maize farming experience and younger age were associated with lower losses by 2.8 and 5.9 percentage points, respectively. Stores where majority of the post-harvest handling decisions were made by women had lower losses by 2.8 percent points. These findings are pointers for the need to strengthen education and mechanisms that enable farmers to put knowledge into practice for effective integrated pest management in farm stores. Highlights: Store hygiene practices during post-harvest handling and storage of maize were assessed. Survey and follow-up of farmers' stores to score hygiene using a standard checklist undertaken. Regression model was used to evaluate the associations between hygiene practices and losses. High store hygiene scores correlated significantly with lower losses. Mechanisms that enable farmers to put knowledge into practice require strengthening.